Nutritional profiles and selected parental factors among children with congenital heart diseases in Ibadan, Nigeria (2015)
"Background: Among the many adverse sequelae of congenital heart disease (CHD), malnutrition stands out as one of the major concerns. Objective: This study was undertaken to compare the nutritional status, parental age, and mid‑parental heights of children with CHD and their apparently healthy control group. Material and Methods: Electrocardiography and echocardiography were used to confirm the presence or otherwise of CHD in consecutive 100 children with CHDs and 100 age, sex, and social class matched apparently healthy control group. Nutritional parameters, parental ages, and mid‑parental heights were also obtained. Associations were tested using student t test and Chi square test. Level of significance was P < 0.05. Results: There were 54 males with CHD and the age‑range of the children was 1–96 months. The commonest acyanotic CHD was ventricular septal defect (49.0%) while the commonest cyanotic CHD was Fallot’s tetralogy (10%). Children with CHD compared with the control group had significantly lower mean z scores for weight for height, height for age, and weight for age. The mid upper arm circumference, triceps, and subscapular skinfold thickness were also lower than that found in the control group. Older parental age and lower mid‑parental heights were found among parents of children with CHD compared with those of controls. Conclusions: Malnutrition can be quite severe in children with CHD if unattended to. Early corrective intervention is necessary to prevent short‑term and long‑term sequelae of malnutrition in these children. Parental malnutrition and older parental age are likely predisposing factors to CHD."